Reactions among Indoor Pollutants - Charles J. Weschler (The Scientific World Journal)
This paper reviews recent studies in the field of “indoor chemistry” — reactions among indoor pollutants. Advances have occurred in a number of areas. A mouse bioassay procedure has shown that ozone/terpene reactions produce products that are more irritating than their precursors, although the agents responsible for the deleterious effects remain to be determined. Indoor ozone/terpene reactions have been demonstrated to produce hydroxyl radicals, hydrogen peroxide, sub-micron particles, and ultrafine particles. New analytical techniques such as LC/MS and thermal desorption mass spectrometry have greatly improved our knowledge of the condensed-phase species associated with such particles. Indeed, the latter approach has identified a number of short-lived or thermally labile species, including organic hydroperoxides, peroxy-hemiacetals, and secondary ozonides, which would be missed by more conventional techniques. Investigators are making inroads into the poorly understood area of indoor heterogeneous chemistry. Systems studied include ozone/HVAC components, ozone/paint, and ozone/carpets. Another heterogeneous process that has been further examined is the indoor formation of nitrous acid through NO2 /surface chemistry. Emissions from indoor sources that contribute to, or are altered by, indoor chemistry have also received attention. Researchers have expanded our awareness of reactive chemicals that can emanate from wood coatings and other products commonly used indoors. In a related vein, a number of recent investigations have shown that emissions from materials can be significantly altered by indoor chemistry. On the theoretical side, an outdoor atmospheric chemistry model has been modified for use as an indoor air model, the effects of ventilation rates on indoor chemistry have been simulated, and initial steps have been taken in applying computational fluid dynamics (CFD) methods to indoor chemistry.